Occupations and Jobs in Cybersecurity and Related Education - Poudin, Konstantin (Research Papers, 2022)
New technologies and their implementation into various spheres of human life are followed by a number of changes. Some of these changes are related to the emergence of new occupations and jobs. The paper aims to present the changes in occupations and jobs, as well as in work positions caused by modern socio-economic and technological conditions. These changes inevitably create new requirements for the education and the training in the specialties related to these new occupations and jobs. The focus is on the cybersecurity occupations, the related education and its quality.